Students Talking Time (STT) Technique to Elevate Speaking Skills in Senior High School Students - Ali, Muhammad Ilham; Ismail, Ismail (Institut Agama Islam Negeri Parepare, 2023)
This study investigates the efficacy of the Student Talking Time (STT) technique in enhancing the speaking skills of second-year senior high school students. Employing a Classroom Action Research (CAR) approach based on Kurt Lewin's cyclic design, the study comprises four phases: planning, acting, observing, and reflecting. Data collection methods include observations, questionnaires, and tests. The findings indicate successful implementation of the STT technique, meeting predefined criteria for success. In the diagnostic test, 12.5% of students achieved the minimal mastery level criterion of Indonesian school, rising to 43.75% in the first cycle's post-test and a remarkable 75% in the second cycle's post-test. Observations reveal increased student confidence and active participation in class discussions and conversations, reflecting improved speaking skills. Questionnaire results indicate high student interest (69.68%) in using the STT technique for speaking practice, with students acknowledging enhancements in their speaking abilities. In conclusion, this study demonstrates the effectiveness of the STT technique in enhancing the speaking skills of senior high school students, as evidenced by improved test scores, heightened confidence, and strong student interest in this teaching approach.